(Im)mobile phones - Alette Schoon; Larry Strelitz (Communicare)
This qualitative study examines the role of the mobile phone in negotiating the day-to-day experience of social immobility for young users in a low-income area in a small town in South Africa. What does the mobile phone become when one is not part of a mobile globalised elite, but poor, unemployed and living on the margins of society in the global south? While research on mobile phones in developed countries suggest these devices facilitate the creation of a society free from the confines of local geography and community, where the user can craft an individualised networked sociability, this may not be the reality in the global south. In our study, mobile phones were seen to amplify a communal sociability where privacy is largely absent from the densely contiguous neighbourhood where life happens on the streets for all to see. This study demonstrates how, in a particular context, mobile phones and the mobile Internet do not necessarily facilitate a mobile world where individual networks allow an escape from local norms and structures, but may instead facilitate communal networks that bind users to the local and the co-present and so facilitate “stuckness”, a term we use to reflect social immobility and the inability to escape the disciplinary surveillance of the co-present.